A = 2 + 2^2 + 2^3 + ... + 2^60
a, A chia hết cho 3
b, A chia hết cho 7 và 15
giải
a, A = 2 + 2^2 + 2^3 + ... + 2^60
= ( 2 + 2^2 ) + ( 2^3 + 2^4 ) + ... + ( 2^59 + 2^60 )
= 2 . ( 1 + 2 ) + 2^3 . ( 1 + 2 ) + ... + 2^59 . ( 1 + 2 )
= 2 . 3 + 2^3 . 3 + ... + 2^59 + 3
= 3 . ( 2 + 2^3 + ... + 2^59 )
=> A chia hết cho 3
b, A = 2 + 2^2 + 2^3 + ... + 2^60
= ( 2 + 2^2 + 2^3 ) + ... + ( 2^58 + 2^59 +2^60 )
= 2 . ( 1 + 2 + 2^2 ) + ... + 2^58 . ( 1+ 2 + 2^2 )
= 2 . 7 + ... + 2^58 . 7
= 7 . ( 2 + ... + 2^58 )
=> A chia hết cho 7
A = 2 + 2^2 + 2^3 + ... + 2^60
= ( 2 + 2^2 + 2^3 +2^4 ) + ... + ( 2^57 + 2^58 + 2^59 +2^60 )
= 2 . ( 1 + 2 + 2^2 + 2^3 ) + ... + 2^57 . ( 1 + 2 + 2^2 + 2^3 )
= 2 . 15 + ... + 2^57 . 15
= 15 . ( 2 + ... + 2^57 )
=> A chia hết cho 15
có chỗ nào không hiểu thì hỏi mình nha